The effect of Cu coated Al2O3 particle content and densification methods on the microstructure and mechanical properties of Al matrix composites - W.S. Barakat; Mohamed I.A. Habba; A. Ibrahim; A. Fathy; Omayma A. Elkady (Journal of Materials Research and Technology, 2023)
In the study, aluminum-based nanocomposites were reinforced with different concentrations of Al2O3 nanoparticles ranging from 0 to 15 wt. %. The Al2O3 nanoparticles were coated by nano Ag and nano Cu by the electroless chemical composition to improve the wettability between the matrix and the reinforcement phase. The influence of the suggested deformation technique and the concentrations of Al2O3 nanoparticles on the microstructure, density, and mechanical properties in terms of hardness and compressive strength of the hot extruded Al/Al2O3 nanocomposites was studied. Results revealed that, as the concentration of nano Al2O3 particles increases, the mechanical properties were improved. XRD, FE-SEM equipped with EDX, and elemental mapping indicates a near-uniform distribution of reinforcement nanoparticles in the matrix. The relative density of the formed nanocomposite recorded a slight decreases than the extruded pure Al. Owing to the presence of the Al2O3 nanoparticles, the Al-15 wt. % Al2O3 hot extruded composite achieves a hardness of 136 and 132 measured on the cross and longitudinal sections, respectively, illustrating an improvement of around 109% over the extruded pure Al. The hot extruded Al/Al2O3 nanocomposites with 5, 10, and 15 wt. % content revealed compressive strength of 564, 579, and 763 MPa, respectively, with an enhancement of 97, 102, and 166% over those of the extruded pure Al.